A Genome-Wide Scan Reveals Important Roles of DNA Methylation in Human Longevity by Regulating Age-Related Disease Genes - Xiao, Fu-Hui (PLoS One, 2015)
It is recognized that genetic factors contribute to human longevity. Besides the hypothesis of existence of longevity genes, another suggests that a lower frequency of risk alleles decreases the incidence of age-related diseases in the long-lived people. However, the latter finds no support from recent genetic studies. Considering the crucial role of epigenetic modification in gene regulation, we then hypothesize that suppressing disease-related genes in longevity individuals is likely achieved by epigenetic modification, e.g. DNA methylation. To test this hypothesis, we investigated the genome-wide methylation profile in 4 Chinese female centenarians and 4 middle-aged controls using methyl-DNA immunoprecipitation sequencing. 626 differentially methylated regions (DMRs) were observed between both groups. Interestingly, genes with these DMRs were enriched in age-related diseases, including type-2 diabetes, cardiovascular disease, stroke and Alzheimer’s disease. This pattern remains rather stable after including methylomes of two white individuals. Further analyses suggest that the observed DMRs likely have functional roles in regulating disease-associated gene expressions, with some genes [e.g. caspase 3 (CASP3)] being down-regulated whereas the others [i.e. interleukin 1 receptor, type 2 (IL1R2)] up-regulated. Therefore, our study suggests that suppressing the disease-related genes via epigenetic modification is an important contributor to human longevity.